A STUDY OF ENGLISH AND UZBEK PROVERBS CONTAINING THE MEDICAL TERMS: A CULTURAL AND LINGUISTIC ANALYSIS - Chorieva Iroda Kurbonboevna (Web of Journals Publishing, 2024)
This study explores the cultural and linguistic significance of proverbs containing the names of medical personnel in English and Uzbek. Through a comparative analysis, it identifies common themes, cultural values, and the role of medical professionals in both societies. The findings reveal how proverbs reflect societal attitudes towards health, medicine, and medical practitioners.
Keywords: Proverbs, medical personnel, doctors, illness, pain, health care, preventive care, culture, language, metaphor, comparison.